Development of endurance of young athletes of 12-13 years in cycling in the initial stage of training - Zh.L. Kozina; K.A. Koval; Yu.K. Vasilyev (H.S. Skovoroda Kharkiv National Pedagogical University, 2019)
The purpose of the research is to develop and substantiate a comprehensive methodology for endurance development of middle school students by means of cycling tourism. Material and methods. This study was attended by cyclists 12-13 years of Lipkutaisha general education school l-lll degrees (9 athletes were experimental group, 9 - control). To determine the functional capabilities of middle school students, the following tests and tests were used: Harvard step-test, Stange test, Genci test, Serkin test. The method of endurance development, which involves the use of a complex of cycling routes, is developed. The complex consists of 2 parts: a complex distance "trials and figured bicycle driving" and a cycling path. The trials represent a distance of 100-200 m in length with natural and artificial obstacles (steep slope, yar, sandy, marsh and other difficult traffic areas, streams, puddles, trunks of trees lying, etc.) along a narrow corridor (up to 1.5 m) , formed by natural and artificial restrictions (ribbons between trees or racks, etc.). Figured bicycle driving involves the use of the following obstacles: "Shaft", "Snake between the stands", "Corridor", "Koliya", "Circle", "Eight", "Gate", "Ring", "Transfer of the object", "Zigzag" , "Swing", "Snake between chips", "Stop-line. Finish". The peculiarity of the campaign is that, in a separate development of endurance, he solved the problem of educational and enlightenment by familiarizing with interesting places of Slobozhanshchyna, meetings with interesting people, and others like that. Results It is shown that the author's method of complex endurance, combining the means of figurehead and cycling, is more effective in comparison with the traditional method of endurance development of middle school students, which contains exclusively the overcoming of distances; It was found that the use of a complex method of endurance development for middle school students contributes to increasing the respiratory detention time for Shtange, Gench, Serkina, as well as reduction of heart rate, heart rate after standard loading and improving the quality of rehabilitation. Conclusion. The developed method can be used in the preparation of young cyclists.